2 fast 2 furious - Moritz, Neal H.; Brandt, Michael, 1968-; Haas, Derek, 1970-; Thompson, Gary Scott; Singleton, John, 1968-2019.; Walker, Paul, 1973-2013; Tyrese; Mendes, Eva, 1974-; Ludacris (Rapper); Universal Pictures (Firm); Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2011)
Now an ex-cop, outlaw racer Brian O'Conner teams up with his ex-con, speed-demon buddy in a bid to clear both their reputations. He hooks up with an undercover agent to bring down a ruthless crime kingpin in a nitro-fueled street racing scene!
Based on characters created by Gary Scott Thompson.
Originally released as a motion picture in 2003.
Bonus features: Inside 2 fast 2 furious; feature commentary; deleted scenes; outtakes; tricking out a hot import car; supercharged stunts.
Music, David Arnold ; editors, Bruce Cannon, Dallas Puett ; director of photography, Matthew F. Leonetti.
Paul Walker, Tyrese Gibson, Eva Mendes, Ludacris.
MPAA Rating: PG-13; street racing, violence, language and some sensuality.
Keywords: Hot rods -- Drama; Automobile racing -- Drama; Automobile racing drivers -- Drama; Undercover operations -- Drama; Criminal behavior -- Drama; Action and adventure films; Thrillers (Motion pictures); Crime films; Film sequels; Feature films; Fiction films; DVD-Video discs; DVDs for the hearing impaired